A Case of Alveolar Capillary Dysplasia with Misalignment of the Pulmonary Veins (ACD/MPV): The Importance of Early Genetic Testing. Issue 1 (March 2021) - Callan, Emily A.; Geddes, Gabrielle; Konduri, Girjia G.; Handler, Stephanie
Alveolar capillary dysplasia with misalignment of the pulmonary veins (ACD/MPV) is a rare, lethal condition caused by irregular pulmonary vascular maturation. Almost all cases present in the newborn period with ensuing respiratory decline within a couple days of life, ultimately leading to nearly 100% neonatal mortality. While the gold standard for diagnosis is lung biopsy, the identification of the Forkhead Box F1 (FOXF1) gene as the main genetic cause of ACD/MPV has allowed for a definitive diagnosis to be made without performing a high-risk procedure in a critically-ill neonate. This case report describes an ACD/MPV patient with hyperinsulinemia and refractory hypoglycemia as well as multiple anomalies who was found to have a novel pathogenic variant in the FOXF1 gene, identified via exome with copy number analysis, which results in premature protein termination (NM 001451.2 c.637 dup, p.Val213Glyfs*82). Our patient showcases the importance of early genetic testing to diagnose ACD/MPV given the substantial risk in obtaining a lung biopsy in a patient with hypoxemic respiratory failure, severe pulmonary hypertension, and vasodilator-induced pulmonary edema.